Caracterização de carne de sol no município de Salinas/Minas Gerais - Alice Ferreira Drummond (2010)
The Carne de Sol is product produced and widely consumed in regions of semi-arid region of Brazil. Due to its historical importance, socio-economic, cultural and health was held in this study to evaluate the physico-chemical, microbiological and production of this product sold in Salinas / MG. We analyzed 40 samples of meat collected from the Sun to retail establishments located in the city of Salinas / MG. The profile of production and processing, were obtained through visits and administering a questionnaire. The results showed that the physical chemistry of Carne de Sol showed values close to the fresh meat with the moisture of 70.13%, 22.35% of protein, 2.25 % of fat, 5.09 of ash and 3,63 of NaCl ,in its portion lean apparent and average pH of 5.8. Variations in physical-chemical parameters were quite significant, especially for levels of salt and ash. Two samples were positive for Salmonella sp. and sixteen (16) had counts above 10 3 for Staphylococcus aureus , these are upper limits to the Brazilian law. As the count of mesophiles, coliforms at 35 ° C , coliforms at 45 ° C and yeasts and molds, the values were 2.50 X 10 7UFC / g, 9.1 MPN / g, 4.3 MPN / g and 1.73 X 10 4 CFU / g respectively. Results 11 related to the questionnaire showed that most producers are men aged 41-50 years not living in the premises, seized the office with their parents, use of wage labor. How to make everyone do not have protocols for the production of beef and Sun, which explains the observed fluctuations in physico-chemical and microbiological contaminants. The results show that the meat Sol de Salinas / MG is a handmade product, with no definite pattern, whose composition resembles fresh meat. It was observed that there is an important micro businesses Meat Sun in Salinas. The producers have shown a willingness to improve the system of production and marketing of this product in the region. These results also show that despite the Beef and Sun have good acceptance by the consumer, it is necessary to create a certification program and guidance hygienic and technological / HST on their production and marketing. This action is shared by most producers because they believe that quality assured expand the sector.